2022
DOI: 10.3390/ijerph191811699
|View full text |Cite
|
Sign up to set email alerts
|

Managing Children’s Fears during the COVID-19 Pandemic: Strategies Adopted by Italian Caregivers

Abstract: Background: Life-threatening events, such as the COVID-19 pandemic, may generate feelings of insecurity and fear in the affected population, particularly children. Parents’ ability to help children cope with negative emotions is essential during challenging periods. The current study aims to analyse the coping strategies adopted by Italian caregivers concerning their children’s fears about COVID-19. Method: An online survey was administered during the Italian lockdown to 649 parents of at least one child aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Support for women, birthing people, and their families should be curated, based on personalised needs assessments in circumstances of high physical, mental, or social risk ( 24 , 25 ). It would also be prudent to not only maintain focus on the health of women and birthing people, but also attend to the established relationship amongst parental, child health, and wider family health, acknowledging the reciprocal nature of the caregiver-infant mental health outcomes ( 44 ) and ensuring healthcare professionals are working holistically ( 31 ) and with the whole family to be proactive and to intervene before families reach crisis point ( 45 ). We must also give greater energy to and focus on those families who find care hard to access ( 46 ); experience high levels of social complexity, inequality, and deprivation ( 47 ); may have a rooted distrust for the NHS and wider social care systems ( 48 ); or are generally underserved by the health and care system ( 49 ).…”
Section: Discussion Of Recommendationsmentioning
confidence: 99%
“…Support for women, birthing people, and their families should be curated, based on personalised needs assessments in circumstances of high physical, mental, or social risk ( 24 , 25 ). It would also be prudent to not only maintain focus on the health of women and birthing people, but also attend to the established relationship amongst parental, child health, and wider family health, acknowledging the reciprocal nature of the caregiver-infant mental health outcomes ( 44 ) and ensuring healthcare professionals are working holistically ( 31 ) and with the whole family to be proactive and to intervene before families reach crisis point ( 45 ). We must also give greater energy to and focus on those families who find care hard to access ( 46 ); experience high levels of social complexity, inequality, and deprivation ( 47 ); may have a rooted distrust for the NHS and wider social care systems ( 48 ); or are generally underserved by the health and care system ( 49 ).…”
Section: Discussion Of Recommendationsmentioning
confidence: 99%
“…According to the National Institute of Mental Health and Neurosciences, the sudden lockdowns, resulting in restricted mobility and isolation, led to stress, irritation, boredom, frustration, and even aggressive behaviors [47]. A number of studies indicated that the most common mental health issues experienced during the pandemic were stress, fear, anxiety, anger, and denial, which were observed both in children and adult populations [48,49]. In response to such negative emotions and states, individuals tended to adopt a variety of coping mechanisms in order to mitigate psychological stress [50].…”
Section: Discussionmentioning
confidence: 99%